How activists respond to social structure in offline and online contexts. - Hartley, Lisa; Lala, G.; Donaghue, N.; Mcgarty, C. (Wiley-Blackwell, 2016)
© 2016 The Society for the Psychological Study of Social Issues. The social identity model of collective action (SIMCA) proposes that collective action flows from identity, perceived injustice, and efficacy beliefs but do these drivers apply for activists in all situations? Intuitively, the social structure that confronts activists should influence when and how they act. In two studies, we consider how activists incorporate the opinions of other people, groups, and institutions as part of their own reality or social structure. In Study 1, quantitative data from 248 activists campaigning for reconciliation between Indigenous and other Australians showed less support for SIMCA when activists faced a divided social movement. In Study 2, qualitative data from 40 online activists suggested that interactions involved identity presentation, used to sharpen and present views of the world and an idealized social structure. Together, findings highlight the practical importance for activists to have a consensual position about social structure, and of activists' efforts to reach that consensus.